2017
DOI: 10.14503/thij-16-6030
|View full text |Cite
|
Sign up to set email alerts
|

Managing Stenotic Septal Perforator Branches

Abstract: Coronary artery disease of the septal perforator branches can lead to clinical ischemia and conduction abnormalities. Performing interventional procedures in these vessels is frequently impossible because they are small, which makes it difficult to approach them and to select appropriate equipment. Larger septal perforator branches have been treated percutaneously in a few patients; however, the clinical effectiveness and long-term outcomes are not known. We present our experience in managing obstructive septa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Although infrequently performed, PCI for SPB has been shown to be feasible in selected patients. 16) In our case, angioplasty for the lethal "jailed" SPB helped to successfully resolve the acute conduction disturbances. Most of the eight published cases demonstrated the following various conduction abnormalities at baseline: first-degree AV block, left bundle branch block, CRBBB, and LAFB.…”
Section: Discussionmentioning
confidence: 62%
“…Although infrequently performed, PCI for SPB has been shown to be feasible in selected patients. 16) In our case, angioplasty for the lethal "jailed" SPB helped to successfully resolve the acute conduction disturbances. Most of the eight published cases demonstrated the following various conduction abnormalities at baseline: first-degree AV block, left bundle branch block, CRBBB, and LAFB.…”
Section: Discussionmentioning
confidence: 62%
“…Without justified invasive intervention, a medical management-only approach can be considered. This approach has been described in an asymptomatic 39-year-old male who presented with NSTEMI, 5800 ng/L troponin I level, and no discernable ischemic EKG changes [9]. CA suggested the culprit lesion involving occlusion of the first SPB.…”
Section: Discussionmentioning
confidence: 96%
“…However, for the same reason, vessels of class S are invasively treated only in exceptional cases and usually play a subordinate role in the perfusion of the heart. 34 Hence, these errors are of limited clinical relevance. Moreover, the retrospective analysis revealed that the moderate performance for the LM segments may have been associated with tracking beyond the ostium into the aorta, causing the ensemble for tree refinement to discard the entire branch in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…These branches are typically short and thin and hence also challenging to identify visually. However, for the same reason, vessels of class S are invasively treated only in exceptional cases and usually play a subordinate role in the perfusion of the heart 34 . Hence, these errors are of limited clinical relevance.…”
Section: Discussionmentioning
confidence: 99%